2013
DOI: 10.1186/1471-2202-14-141
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell-free adult canine olfactory ensheathing cell preparations from olfactory bulb and mucosa display differential migratory and neurite growth-promoting properties in vitro

Abstract: BackgroundTransplantation of olfactory ensheathing cells (OEC) and Schwann cells (SC) is a promising therapeutic strategy to promote axonal growth and remyelination after spinal cord injury. Previous studies mainly focused on the rat model though results from primate and porcine models differed from those in the rat model. Interestingly, canine OECs show primate-like in vitro characteristics, such as absence of early senescence and abundance of stable p75NTR expression indicating that this species represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…OEC transplantation has been shown to promote regeneration and functional recovery in lesioned spinal cord [9,10]. In that the regenerative properties of OECs are largely associated with their migration and lamellipodial dynamics (e.g., [23,69]) there is a considerable interest in enhancing OEC migratory capacity. In fact, it is assumed that OECs migrate ahead of growing axons and by secreting supporting factors (e.g., GDNF) [16,28], or with matrix metalloproteinase activity [70] aiding and promoting their elongation.…”
Section: Discussionmentioning
confidence: 99%
“…OEC transplantation has been shown to promote regeneration and functional recovery in lesioned spinal cord [9,10]. In that the regenerative properties of OECs are largely associated with their migration and lamellipodial dynamics (e.g., [23,69]) there is a considerable interest in enhancing OEC migratory capacity. In fact, it is assumed that OECs migrate ahead of growing axons and by secreting supporting factors (e.g., GDNF) [16,28], or with matrix metalloproteinase activity [70] aiding and promoting their elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Primary damage occurs by mechanical tissue disruption immediately subsequent to trauma. Secondary damage is mediated by complex cellular and molecular processes (Roloff et al 2013). NT-3, as one of the important neurotrophic factors, modulates neuron cell growth, differentiation and survival (Brodski et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis indicated gene expression of brain-derived neurotrophic factor (BDNF), NGF and neurotrophin-3 in both groups, but the secretion levels of these growth factors were increased in OM-OECs . Moreover, in an in vitro study, OB-OECs and SCs displayed faster migratory properties and more effective neuritic outgrowth of cocultured human NT2 neurons than OM-OECs, further indicating the physiological differences between OM-OECs and OBOECs [Roloff et al, 2014].…”
Section: Heterogeneity Of Om-oecs and Ob-oecs In Vagus And Recurrentmentioning
confidence: 99%
“…It was demonstrated that OM-OECs overexpress genes characteristic of wound healing and regulation of the extracellular matrix. Moreover, in an in vitro study it was demonstrated that OB-OECs and SCs displayed faster migratory properties and more effective neuritic outgrowth than OM-OECs, whereas all three glial cell types demonstrated similar phagocytic effects [Roloff et al, 2014]. With regard to their origin-dependent functional characteristics, cotransplantation of both subpopulations in a recurrent laryngeal nerve injury model resulted in enhanced functional recovery by the transplantation in combination with a reduction of synkinesia, indicating a complementary and superior effect when transplanted combined [Guérout et al, 2011a].…”
Section: Heterogeneity Of Om-oecs and Ob-oecs In Vagus And Recurrentmentioning
confidence: 99%
See 1 more Smart Citation